The Relationship Between Social Media Dependency, Mental Health, and Academic Performance Among Adolescents in Indonesia - Zani, Benny Novico; Said, Faridah Mohd; Nambiar, Nisha; Sholihat, Siti (STIKep PPNI Jawa Barat, 2024)
Aims : the purpose of this study was to investigate the relationship between social media addiction, mental health, and academic performance among adolescents in Depok, Indonesia. Methods : A cross-sectional study was conducted in senior high school students in Depok, West Java, among teenagers aged 15-18 years. The Social Media Addiction Scale-Student Form (SMAS-SF) Questionnaire scale, the Depression Anxiety Stress Scale (DASS), and the Social Media and Academic Performance of Students (SMAAPOS) were the scales employed. Results : The mean age of the 200 adolescents in the intervention group was 16.37 (SD+2.55), with 60% being male. With an average score of 88.43 (SD=24.53), respondents demonstrated a moderate level of social media dependency. The respondents' mental health score dropped from 21.37.78 to 90.2137.24, and their academic performance was mediocre. Social media dependency (r=0.241) and sadness (r=0.405) were found to be substantially related to academic performance. Conclusions : correlation between social media addiction and mental health problems (r=0.334) was discovered. Supportive social environments and social networks, as well as improved emotional regulation and resilience in the face of stress and adversity, are central goals of interventions for the promotion and prevention of mental illness.